Evaluating Large Bank Risk Using Stock Market Measures in the Basel III Period. Issue 1 (24th June 2022) - Song, Guoxiang
Abstract: There is a puzzle in the literature which seems to indicate that high capital levels introduced by Basel III increase bank risk. This paper attempts to solve this puzzle by investigating whether the risk of the eight U.S. global systemically important banks (GSIBs) increased in the Basel III period from previous periods. This paper uses case studies of the eight U.S. GSIBs to evaluate whether Basel III has changed their risk perceived by the market. Basel III has reduced the systematic risk of equity of U.S. GSIBs perceived by the stock market, and it does not explain the decline in return on equity (ROE) which may indicate some increase in large bank financial risk. The paper breaks down stock market measures into drivers which capture systematic risk of equity and other drivers which capture financial risk, and it finds new evidence which solves the puzzle in the literature on large bank risk. The findings of the paper help investors, creditors and regulators to have a clear understanding of the market perception of large bank risk. The paper provides new methods and evidence which could help regulators to assess the impact of Basel III on bank risk perceived by the market.